Development of Mental Health Early Detection Skills for Regional Soul Cadres - Ratna Yunita Setiyani Subardjo; Zahro Varisna Rohmadanai (Urecol Journal. Part H: Social, Art, and Humanities, 2021)
Mental disorders are still a serious mental health problem in Indonesia. The 2013 Riskesdas results state that DIY is in the first place for the highest level of mental disorders in Indonesia. It is a challenge in itself for the DIY government to make efforts from all sides in order to improve the dignity and dignity of people with mental disorders, both preventive, promotive, curative and rehabilitative. One area in DIY where the level of mental disorders is still high is the Kraton District area. This is evidenced by the data from the Kraton Subdistrict Health Center that there are about 661 people who are exposed to mental disorders and various mental problems out of 22,502 residents. 661 people who were exposed, as many as 53 people were diagnosed with schizophrenia (serious mental disorders. Most of the people in the Kraton sub-district are elderly and migrants. fear, until there are delusions and hallucinations that can lead to the emergence of new mental disorders for families Promotional and preventive efforts are still very rare because people lack knowledge of the definition of mental disorders, especially how to recognize symptoms that can be used as markers for early detection. Therefore, the authors propose to hold training on early detection of mental disorders to community groups in the Panembahan and Patehan areas in the Kraton sub-district, Yogyakarta. This is because there are quite a lot of mental disorders in the area. This training is provided by involving experts in the health sector. psychologists and psychiatrists as well as policy observers. It is planned to be given four times. The hope is that it can help the community improve the mental health of their area by opening a network with the Puskesmas, becoming a Puskesmas program that can reduce the vulnerability of the local community. This program is also expected to contribute more broadly to reducing the level of mental disorders in the Yogyakarta City / DIY area by advocating for the Yogyakarta City Health Office and the Yogyakarta City Parliament.